Acute Rhabdomyolysis Associated with Coadministration of Levofloxacin and Simvastatin in a Patient with Normal Renal Function. (22nd July 2014) - Paparoupa, Maria; Pietrzak, Sebastian; Gillissen, Adrian
Abstract : We report a rare case of severe acute rhabdomyolysis in association with coadministration of levofloxacin and simvastatin in a patient with normal renal function. A 70-year-old Caucasian male was treated due to community acquired pneumonia with levofloxacin in a dosage of 500 mg once and then twice a day. On the 8th day of hospitalization the patient presented with acute severe rhabdomyolysis requiring an intensive care support. After discontinuation of levofloxacin and concomitant medication with simvastatin 80 mg/day, clinical and laboratory effects were totally reversible. Up to now, levofloxacin has been reported to induce rhabdomyolysis mainly in patients with impaired renal function, as the medication has a predominant renal elimination. In our case renal function remained normal during the severe clinical course. According to a recent case report rhabdomyolysis was observed due to interaction of simvastatin and ciprofloxacin. To our best knowledge this is the first case of interaction between simvastatin and levofloxacin to be reported. This case emphasizes the need of close monitoring of creatine kinase in patients under more than one potentially myotoxic medication especially when patients develop muscle weakness.